How sales and sales management are changing - Rogers, Beth (Henry Stewart Talks, 2010)
The role of personal selling, Sales standard, How the environment for selling has changed, The effects of change on the value creation imperative, New methods of sales, Resource management, The skills gap, The strategic role of sales characteristics of the profession, The challenge of change